A critical analysis of employment equity measures in South Africa - Laher, Ismail (Rhodes University, Faculty of Law, Law, 2007)
This thesis analyses the Employment Equity Act 55 of 1998 and its application in labour law in South Africa. After an initial examination of the general concepts with regards to employment equity and current international conventions regarding employment equity, the study will move on to examine employment equity as it stands in the law today. In examining the current law regarding employment equity, a brief historical background will be offered in order to show the legacy of apartheid: the immense disparity between the different categories of South African people in the modern era. By using this background and analysing the relevant provisions of the Constitution, it will be argued that there is a very real need for employment equity measures to bring about a true sense of equality in South Africa and that such measures are fully endorsed by the Constitution. After it has been established that affirmative action is an important tool in the creation of an equal South Africa, the measures put in place to help create this equal South Africa will be critically analysed. This critical analysis will point out certain weaknesses in the current affirmative action system. Following this critical analysis of the South African employment equity law, the employment equity systems used in Brazil, Canada and Malaysia will be examined in detail. The purpose of this analysis will be to find the strengths and weaknesses and successes and failures of these foreign systems. This will be done in order to highlight those areas of the foreign systems that can be implemented into South African law in order to make the South African employment equity system stronger. The weaknesses of those systems will also be highlighted in order to learn valuable lessons from other system's failures so that South Africa does not make the same mistakes. The final part of this thesis will be in depth discussions and the proposal of solutions to the weaknesses of the South African employment equity system that have been highlighted throughout the thesis. These proposals will be put forward in order to ensure the most efficient and effective employment equity system in South Africa. There will also be a reassessment of the most valuable lessons learned from the foreign systems that would be easily implemented into or avoided by the South African system in order to ensure an effective employment equity system. The purpose, therefore, of this thesis is to critically analyse employment equity in South Africa. A further purpose will be to propose certain amendments and changes to the current system to ensure the Employment Equity Act is reflective of the needs of the people South Africa.
Keywords: South Africa. Employment Equity Act, 1998; Labor laws and legislation -- South Africa; Discrimination in employment -- Law and legislation -- South Africa; Affirmative action programs -- Law and legislation -- South Africa